A structure model of economic resilience on female single-parent families: The contribution of digital inclusion, financial management and financial trauma - Sutanto, Hermawan; Handayani, Fitri; Sofyan, Silvia (Universitas Ahmad Dahlan, 2025)
Female single-parent households are among the most vulnerable groups to economic shocks due to limited access to resources, decent work, and social protection. Strengthening their economic resilience is therefore a pressing challenge, particularly in the era of digitalization where opportunities and risks coexist.This study aims to examine the role of digital inclusion, financial management, and financial trauma in shaping the economic resilience of female-headed households in Medan.The research contributes to the literature by integrating digital and psychosocial dimensions into a structural model of economic resilience, while also offering evidence-based insights for inclusive empowerment policies.A quantitative approach was employed using a survey of 200 respondents, and data were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS).The results indicate that digital inclusion significantly improves financial management and directly enhances economic resilience. Financial management mediates the relationship between digital inclusion and economic resilience, showing that digital access only translates into stronger resilience when supported by effective financial practices. Financial trauma, while directly influencing economic resilience, was not found to moderate the link between financial management and resilience.In conclusion, the findings highlight that access to digital technology combined with strong financial management skills is the key to building sustainable economic resilience in female-headed households.